Estudo da geração de nanopartículas a partir da atomização de soluções de cloreto de sódio - Amaral, Clarice Dias do (2010)
Particles of nanometric dimensions are subjected, in recent years, to extensive research all over the world, not only for the possible risks that they cause when inhaled, but also for the wide range of applications and improvements obtained with their employment. An interesting and economical form of generating these particles in the nanometric scale is through the atomization of a salt solution. With the atomization of the solution, a cloud of drops is generated, which is subsequently evaporated by heat exchange with the surrounding gas. The salt nanoparticles are then incorporate in the flowing gas, forming an aerosol. In this method, the size of the particles can be controlled by changing the concentration of the atomized solution. The present work had as objective the study of this generation mechanism. This study was made through the investigation of the size distributions of drops and particles at different salt concentrations. The nanoparticles were generated through the atomization of solutions of sodium chloride that were characterized regarding their density, viscosity and surface tension. In the atomization process two different atomizers were utilized. They were made of different material and geometry, but both were twin-fluid (gas-liquid) atomizers. One of the atomizers was built in the at DEQ-UFSCar and the other was a commercial inhalator named NS. The measurements of drop size distribution were made using the equipment Malvern Spraytec. The distribution of sizes and concentration of the particles were obtained through the electrical mobility particle analyzer SMPS, from TSI, where the sampling was made directly from the aerosol. The results showed that the increase in the concentration of the saline solution resulted in an increase of the particles median diameter. Also, an increment in the number of particles was observed with the increase in the saline solution concentration. The drop size distribution was associated to the physical properties of each solution and they did not show considerable variations as the solution of NaCl became more concentrated. These results discard the possibility that the number of particles increases due to an increment in the number of drops with salt concentration, since their size was virtually the same in all tests performed. The increase in the total number of nanoparticles is probably due to the drying mechanism of the drops. It was evidenced that a single drop generates more than a particle and that tendency increases with the concentration of the saline solution, tending asymptotically to a constant value. An empiric expression correlating the number of particles generated to the saline concentration of the atomized solution it is proposed and it represents well the experimental data.